Cultural values in political economy - Singh, J. P., 1961- (Stanford University Press, 2020)
"Cultural anxiety and anger are often linked in the media to economic pressures. From headlines about the global rise in populism to the effects of trade and migration, the connections between cultural contexts and political conditions have never been clearer. This book maps those connections, exploring culture's influence as implicit and explicit, utilitarian and symbolic, and constant and changing. Contributors offer multiple historical, disciplinary, and methodological lenses to provide a comprehensive understanding of the ways cultural interests are imbricated in political economy. Addressing a range of flashpoints, including environmental responsibility, cosmopolitanism and parochialism, higher education, American exceptionalism, the religious right, and soft power, Culture and Political Economy provides useful ways to deepen our understanding of political economic change and global politics more broadly"--